2015
DOI: 10.1039/c5ra00194c
|View full text |Cite
|
Sign up to set email alerts
|

Role of pentahedrally coordinated titanium in titanium silicalite-1 in propene epoxidation

Abstract: Role of pentahedrally coordinated titanium in titanium silicalite-1 in propene epoxidationA new pentahedrally coordinated Ti was discovered in TS-1 and showed a higher catalytic activity than the tetrahedrally coordinated one.Two titanium silicalite-1 samples with different crystal sizes were synthesized in the tetrapropylammonium bromide (TPABr) and tetrapropylammonium hydroxide (TPAOH) hydrothermal systems. The small-crystal TS-1 with a size of 600 nm was then treated with different organic bases. These TS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 48 publications
3
55
0
1
Order By: Relevance
“…In several liquid-phase epoxidation routes to convert propene into propene oxide, much attention has been directed to heterogeneous catalytic oxidation using hydrogen peroxide as a more environmentally benign and profitable chemical process [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium silicalite (TS-1) catalyst has been extensively investigated for this route because propene oxide can be produced with a high selectivity in methanol under mild conditions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The direct epoxidation process based on hydrogen peroxide (oxidant) and TS-1 (catalyst) was commercialized and referred to as "hydrogen peroxide-to-propene oxide" (HPPO) process.…”
Section: Introductionmentioning
confidence: 99%
“…In several liquid-phase epoxidation routes to convert propene into propene oxide, much attention has been directed to heterogeneous catalytic oxidation using hydrogen peroxide as a more environmentally benign and profitable chemical process [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium silicalite (TS-1) catalyst has been extensively investigated for this route because propene oxide can be produced with a high selectivity in methanol under mild conditions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The direct epoxidation process based on hydrogen peroxide (oxidant) and TS-1 (catalyst) was commercialized and referred to as "hydrogen peroxide-to-propene oxide" (HPPO) process.…”
Section: Introductionmentioning
confidence: 99%
“…attributed it to isolated Ti species that coordinate with two water molecules 41. We also studied the assignment of this band of Ti in our previous work,30, 42 and found that at least two kinds of Ti species existed in this region. We conclude that the band at λ =250–280 nm in the samples in this work can be attributed to Ti coordinated octahedrally formed by one Ti coordinated tetrahedrally that bonds with two water molecules.…”
Section: Resultsmentioning
confidence: 68%
“…The other important factor that influences the catalytic performance of TS‐1 is the coordination state of Ti and the diffusion properties. Ti coordinated tetrahedrally is the primary active center for selective oxidation, and we found that Ti coordinated pentahedrally showed a higher activity than tetrahedral Ti 30. However, the synthesis of TS‐1 with a high content of pentahedral Ti is difficult.…”
Section: Introductionmentioning
confidence: 92%
“…The dominant band centered at 210 nm is assigned to the Ti 4+ O 2− to Ti 3+ O − ligand‐to‐metal charge transfer, and is characteristic of isolated tetrahedrally coordinated Ti atoms in framework . No adsorption bands attributed to octahedrally coordinated Ti containing Ti‐O‐Ti bond or isolated Ti species coordinated water molecules are observed at 240–290 nm. In addition, there is no adsorption band at 330 nm, indicating the absence of extra framework anatase TiO 2 .…”
Section: Resultsmentioning
confidence: 99%